Sympathetic components in left and right human cervical vagus nerve: implications for vagus nerve stimulation - Ruigrok, Tom J. H.; Mantel, Sophia A.; Orlandini, Lara; de Knegt, Corné; Vincent, Arnaud J. P. E.; Spoor, Jochem K. H. (Frontiers in Neuroanatomy, 2023)
Cervical vagus nerve stimulation is in a great variety of clinical situations indicated as a form of treatment. It is textbook knowledge that at the cervical level the vagus nerve contains many different fiber classes. Yet, recently, several reports have shown that this nerve also may contain an additional class of potentially noradrenergic fibers, suggested to denote efferent sympathetic fibers. As such, the nature and presence of these fibers should be considered when choosing a stimulation protocol. We have studied human vagus material extracted from dissection room cadavers in order to further confirm the presence of this class of fibers, to study their origin and direction within the nerve and to determine their distribution and variability between subjects and pairs of left and right nerves of the same individual. Sections were studied with immunohistochemical techniques using antibodies against tyrosine hydroxylase (TH: presumed to indicate noradrenergic fibers), myelin basic protein and neurofilament. Our results show that at least part of the TH-positive fibers derive from the superior cervical ganglion or sympathetic trunk, do not follow a cranial but take a peripheral course through the nerve. The portion of TH-positive fibers is highly variable between individuals but also between the left and right pairs of the same individual. TH-positive fibers can distribute and wander throughout the fascicles but maintain a generally clustered appearance. The fraction of TH-positive fibers generally diminishes in the left cervical vagus nerve when moving in a caudal direction but remains more constant in the right nerve. These results may help to determine optimal stimulation parameters for cervical vagus stimulation in clinical settings.